Answer:
x=14
y=27
z=43
Step-by-step explanation:
hope it helps!
Answer:
Your selection is appropriate
Step-by-step explanation:
A negative exponent in the numerator is equivalent to a positive exponent in the denominator, and vice versa.
... a⁻² = 1/a²
____
2⁴ multiplies the variable expression no matter which way it is written.
Answer:
19 6j/5
Step-by-step explanation:
The answer is B: a^3b^4<span>
Proof:
Simplify the following:
(a^7 b^8)/(a^4 b^4)
Combine powers. (a^7 b^8)/(a^4 b^4) = a^(7 - 4) b^(8 - 4):
a^(7 - 4) b^(8 - 4)
7 - 4 = 3:
a^3 b^(8 - 4)
8 - 4 = 4:
Answer: a^3 b^4
PS: I just wish that you put the equation down as it's intended i.e.
a^7b^8/a^4b^4 is not the same as (<span>a^7b^8)/(a^4b^4)</span>
</span>